2014
DOI: 10.1007/s00167-014-2892-x
|View full text |Cite
|
Sign up to set email alerts
|

Similar stability and range of motion between cruciate-retaining and cruciate-substituting ultracongruent insert total knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 16 publications
8
41
0
Order By: Relevance
“…25,35 Although this is thought to lead directly to greater instability, this causative relationship has not been objectively demonstrated in vivo. Furthermore, Lützner et al 33 found similar intraoperative stability between the two constructs, with no statistical difference. Despite the difference in femoral rollback, both PS and CR TKAs have been proven to provide a similar improvement in stability both intraoperatively and for outcome scores postoperatively.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…25,35 Although this is thought to lead directly to greater instability, this causative relationship has not been objectively demonstrated in vivo. Furthermore, Lützner et al 33 found similar intraoperative stability between the two constructs, with no statistical difference. Despite the difference in femoral rollback, both PS and CR TKAs have been proven to provide a similar improvement in stability both intraoperatively and for outcome scores postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…Even though a statistically significant difference in ROM between PS and CR groups was detected, both the underreporting of results and the difference in follow-up times may influence our results. For example, there were differences in the definition of postoperative, most reporting at 2 years 5,8,19,23,28,30,32,33,36,38,40,42,43,45 and some at 5 years. 2,3,9,14,17 Also, it is difficult to know at what time assessment was undertaken postoperatively for those who did not clarify their methods of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous cadaver study compared the biomechanics of intact, CR and CS TKR during simulated stair‐descent loading, and noted a substantial anterior femoral shift of the CS TKR knees (without a PCL), which agrees with the current study. Generally speaking, however, most clinical studies have found that there is little to no difference in the clinical outcomes of CR bearings with a PCL versus CS (or ultra‐congruent) bearings without a PCL . The fact that findings from in vitro cadaver studies do not seem to present clinically in the form of any functional disability may be due to simplifications and abstractions from the real loading scenario; or, on the clinical side, insensitivity to relatively small changes in joint laxity or post‐operative muscle compensation to stabilize the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Although further evaluations are required, intraoperative navigation can measure knee kinematics during surgery and may assist surgeons to optimize knee kinematics or identify abnormal knee kinematics that could be corrected with ligament releases to improve the functional result of TKA. 23 Lützner et al 24 evaluated stability and ROM in standard cruciate-retaining (CR) and cruciate-substituting UC inserts of the same TKA. Their study demonstrated similar mediolateral laxity with the UC insert compared with the CR insert.…”
Section: Discussionmentioning
confidence: 99%